Summary of the New England conference on legal and institutional incentives to small-scale hydroelectric development (Boston Massachusetts, January 30-31, 1979) (Energy Law Inst., Concord, NH (USA). Franklin Pierce Law Center, 1980)
The New England Conference on Legal and Institutional Incentives to Small Scale Hydroelectric Development examined the legal and institutional problems confronting small-scale hydroelectric potential of the northeast. Representatives from DOE, FERC, state legislatures, state public service commissions, private developers, and environmental groups attempted to evaluate the state of hydroelectric development in New England. The meeting began with an introductory panel followed by workshops addressing four topics: Federal regulatory systems, state regulatory systems, the economics of small-scale hydroelectric development, and systems dynamics and the systems dynamics model. Comments by the Honorable Georgiana H. Sheldon, FERC, are presented.